Предмет: Математика, автор: dasha150410

(x - 2)² + (x - 2) - 10=0
Решите пожалуйста

Ответы

Автор ответа: svetazuna
0

Пошаговое объяснение:

(x - 2)² + (x - 2) - 10 = 0,

1 способ:

(x - 2)² + (x - 2) - 10 = 0,

х² - 4х + 4 + х - 2 - 10 = 0,

х² - 3х - 8 = 0,

Д = (-3)² - 4*1*(-8) = 9 + 32 = 41,

х1 = (3 + √41) / 2*1 = (3+√41)/2,

х2 = (3 - √41) / 2*1 = (3-√41)/2,

2 способ:

(x - 2)² + (x - 2) - 10 = 0,

пусть х-2 = а, тогда:

а² + а - 10 = 0,

Д = 1² - 4*1*(-10) = 1 + 40 = 41,

а1 = (-1 + √41) / 2*1 = (-1+√41)/2,

а2 = (-1 - √41) / 2*1 = (-1-√41)/2,

х1 - 2 = а1,

х1 - 2 = (-1+√41)/2,

х1 = (-1+√41)/2 + 2 = (-1+√41)/2 + 4/2 = (-1+√41 + 4)/2 = (3+√41)/2,

х2 - 2 = а2,

х2 - 2 = (-1-√41)/2,

х2 = (-1-√41)/2 + 2 = (-1-√41)/2 + 4/2 = (-1-√41 + 4)/2 = (3-√41)/2,

Похожие вопросы
Предмет: Математика, автор: kristinakoboze